2016
DOI: 10.1177/1082013216642049
|View full text |Cite
|
Sign up to set email alerts
|

High hydrostatic pressure as a method to preserve fresh-cut Hachiya persimmons: A structural approach

Abstract: The "Hachiya" persimmon is the most common astringent cultivar grown in California and it is rich in tannins and carotenoids. Changes in the microstructure and some physicochemical properties during high hydrostatic pressure processing (200-400 MPa, 3 min, 25 ℃) and subsequent refrigerated storage were analyzed in this study in order to evaluate the suitability of this non-thermal technology for preservation of fresh-cut Hachiya persimmons. The effects of high-hydrostatic pressure treatment on the integrity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…These clusters have also been detected in mango and carrot tissue [41] and in persimmon. [42,43] PEF treatment caused structural modifications in both, outer and inner parenchyma of carrot (Figure 3). PEF caused the breakdown and degradation of cell walls and membranes (Figure 3a and b).…”
Section: Effect Of Pef On Carrot Microstructurementioning
confidence: 99%
“…These clusters have also been detected in mango and carrot tissue [41] and in persimmon. [42,43] PEF treatment caused structural modifications in both, outer and inner parenchyma of carrot (Figure 3). PEF caused the breakdown and degradation of cell walls and membranes (Figure 3a and b).…”
Section: Effect Of Pef On Carrot Microstructurementioning
confidence: 99%
“…Furthermore, HPP may either enhance (leading to enzymatic browning reactions due to loss of membrane permeability and sub-cellular compartmentalization) or inhibit the activity of enzymes related to cell wall degradation in FC products [209]. HPP treatment (200-400 MPa, 3 min, 25℃) of FC persimmon induced changes in physicochemical quality (electrolyte leakage, texture, total soluble solids, pH, and color), which were a function of the amount of applied pressure compromising the consumer acceptance of the product [210]. However, latter authors reported that HPP may improve carotenoid extractability and tannin polymerization of FC persimmon, which could enhance its functionality and eliminate astringency, respectively.…”
Section: High-pressure Processingmentioning
confidence: 99%
“…Kumari et al also observed that persimmon pulp treated by HPP under 20 °C/400 Mpa/5 min had a reduced total plate count and yeast mold count [ 8 ]. Moreover, José et al studied HPP under 200 Mpa for improved carotenoid extractability and tannin polymerization in order to improve the functionality and taste of fresh-cut persimmon [ 9 ]. Similar results were studied by de Ancos et al [ 10 ], Lucía et al [ 11 ] and Cano et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%